THE REFORM OF THE COMMON AGRICULTURAL POLICY AFTER 2013 – ADJUSTING THE INSTRUMENTS TO THE STRATEGIC PLAN FOR AGRICULTURE AND RURAL DEVELOPMENT - Sadłowski, Adrian (Acta Scientiarum Polonorum. Oeconomia, 2012)
The article deals with the issue of the reform of the Common Agricultural Policy (CAP) after 2013, especially with its relation with the strategic development plan of the European Union. The first part of the study presents an overview of the objectives of the CAP in the new financial perspective. The objectives are supposed to be a response to emerging new challenges. Then there is a presentation of the reform scenarios considered by the European Commission. They provide for the adjustment of the policy tools to the long-term development plan. This was the starting point for the exegesis of the strategic objective of the CAP. The conclusion states that designing the policy tools focused on the long-term goal of the CAP requires balancing the objectives related to the efficiency of agriculture in the production of market goods with the objectives related to the efficiency of this sector in delivering public goods.